Cloning, expression, purification, crystallization and preliminary X‐ray studies of argininosuccinate lyase (Rv1659) from Mycobacterium tuberculosis. Issue 12 (1st December 2013) - Paul, A.; Mishra, A.; Surolia, A.; Vijayan, M.
<x xml:space="preserve">Abstract</x> The last enzyme in the arginine‐biosynthesis pathway, argininosuccinate lyase, from Mycobacterium tuberculosis has been cloned, expressed, purified and crystallized, and preliminary X‐ray studies have been carried out on the crystals. The His‐tagged tetrameric enzyme with a subunit molecular weight of 50.9 kDa crystallized with two tetramers in the asymmetric unit of the orthorhombic unit cell, space group P212121. Molecular‐replacement calculations and self‐rotation calculations confirmed the space group and the tetrameric nature of the molecule.